A PRAGMATIC STUDY OF ENTICEMENT IN MEDICAL MARKETING - Assist. Lect. Israa Abed Jawad, Assist. Lect. Alaa Auda Ali, Assist. Lect. Dina Qusay Ismael, Lect. Sabah Nimma Faraj, Assist. Lect. Diana Sabah Nimma (Journal of Daoist Studies, 2026)
Medical marketing is rising rapidly due to the rising of the technology and online education with a severe competition. The current study investigates medical marketing by examining the official websites of some well-known British medical schools to identify the pragmatic strategies employed to convey enticing meanings for students targeted to join these schools’ courses. The current study attempts to answer four research questions: 1. What are the speech acts mostly employed to entice students targeted? What are the politeness strategies employed to entice customers in the medical advertisements under analysis? What are the Rhetorical strategies mostly employed to entice customers in the medical advertisements under analysis? What are the Rhetorical appeals mostly employed to entice customers in the medical advertisements under analysis? To answer these questions, the researcher adopts an eclectic model composing Searl’s (1969) speech acts, Brown and Levinson’s (1987) politeness, Rhetorical strategies and appeals as explained in section 2. The analysis revealed that the medical schools concerned have relied heavily on promising and offering speech acts with the positive politeness strategy 10 to assert offering and promising acts. Rhetorical strategy dominated other strategies is overstatement which intensifies any positive traits mentioned. Finally, all rhetorical appeals are employed with logos prominent to show factual points enticing students rather than imaginative or hypothetical stories. The researcher recommends the English curriculum designers to highlight the uses of speech acts, politeness strategies, rhetorical appeals and strategies as marketing strategies to entice customers.